IMPLIKASI POLA ASUH ORANG TUA DALAM PENUMBUHKEMBANGAN KARAKTER ANAK USIA DINI - Sunariyadi, Nyoman Sri; Yuni Andari, Ida Ayu Made (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Parenting patterns to develop children's character education require extra coaching and supervision efforts by parents. So it is necessary from the character education needed by children. In this study using descriptive research with qualitative methods. In the research conducted in Ubung Kaja Village, it was found that parents instill the character of tolerance from children from an early age, parents also instill a communicative character in socializing with others and instill the value of religious teachings, namely Tri hita Karana by increasing the character of caring for the environment by watering plant.